EFL Speaking Anxiety among Senior High School Students and Policy Recommendations - Amirul Mukminin; Masbirorotni Masbirorotni; Noprival Noprival; Sutarno Sutarno; Nelly Arif; Maimunah Maimunah (Journal of Education and Learning (EduLearn), 2015)
This report drew on a larger study which was to describe and understand the sources of senior high school students’ English language speaking anxiety at senior high schools in Jambi, Indonesia. The purpose of this paper was to report some of findings from the qualitative interview data on the sources of senior high school students’ English language speaking anxiety at one senior high school in Jambi, Indonesia. Data were collected through demographic profiles and semi-structured interview with senior high school students. The demographic data were analysed descriptively while the interview data were transcribed and analysed line by line to generate and develop codes and themes. An analysis of the interview data revealed that five major themes were related to students’ English language speaking anxiety, including (1) low speaking skill due to lack of vocabulary and grammar, (2) fear of negative responses from others, (3) low self-esteem to speak in English, (4) fear of being evaluated by teachers, and (5) cultural influences to speak English due to a more teacher-centred style. Suggestions and policy implications are also discussed.